THE ROLE OF INNOVATIVE INTERNET MARKETING TOOLS IN THE PROMOTION OF A TOURIST PRODUCT - Barvinok , N. V. (The actual problems of regional economy development, 2021)
The article considers the importance of introducing an innovative approach to marketing to promote the tourist product in the market of tourist services in the context of globalization and informatization of the modern economy and society as a whole. The market of virtual space is open and accessible to both businesses and consumers, then such a market is global, ie accessible from anywhere in the world. Commercial success of innovations is impossible in the market without active support of marketing and the Internet, so the importance and role of the virtual world, and especially Internet marketing, to attract and retain customers to sell a tourism product in the services market. The purpose of the article is to determine the role of innovative tools of Internet marketing in the promotion of tourism products. Research methods. The methods of system approach, logical modeling, logical deduction, induction of interaction with the methods of classification and cognitive structuring were used in the research, which allowed to reveal the essence of the innovative approach of marketing to the promotion of the tourist product. Results. In the article on the basis of the processed literature sources of foreign and domestic scientists on the role of innovative Internet marketing tools it is established that there is no single unified structure of innovative Internet marketing tools in promoting an innovative product, identified and structured the main innovative tools for Internet marketing The main task of marketing in the tourism sector - the promotion of tourism products, studied current trends in the use of innovative tools of Internet marketing in tourism, considered the possibility of promoting tourism products with innovative Internet marketing tools that open the possibility of selling tourism products through the global Internet , substantiated and formulated the main aspects of the use of the virtual environment for effective and promising activities of tourism enterprises in order to increase their competitiveness those. Practical meaning. Priority innovative Internet marketing tools are proposed, which in the future will help to clearly form programs and strategies focused on the virtual vector of development of Internet marketing tools in the field of tourism.